A new type of dual temperature sensitive triblock polymer (P(AM-co-AN)-b-PDMA-b-PNIPAM) and its self-assembly and gel behavior. (17th March 2021) - Zhou, Cheng; Chen, Yan; Huang, Mingjun; Ling, Yi; Yang, Liming; Zhao, Guochen; Chen, Jie
Abstract : A dual-action polymer (P(AM- co -AN)- b -PDMA- b -PNIPAM) and its sol–gel behavior only through simple temperature changes. Abstract : A dual temperature-responsive triblock polymer (poly( N -isopropyl acrylamide)- block -poly( N, N -dimethyl acrylamide)- block -poly(acrylamide- co -acrylonitrile)) (P(AM- co -AN)- b -PDMA- b -PNIPAM) (NDAA) was obtained by sequential reversible addition–fragmentation chain transfer (RAFT) polymerization, with the uncharged UCST temperature-sensitive block P(AM- co -AN) and the classic LCST-type temperature-sensitive block PNIPAM. This well-defined thermo-responsive copolymer with tunable compositions exhibits a dual thermal response behavior in water. Properly designing the length of the block can make the block copolymer undergo a phase transition within the envisaged temperature range. When the concentration is 5 wt%, the UCST of the NDAA polymer is around 20 °C, and the LCST is around 31 °C. All three blocks of these polymers are soluble in water within 20–31 °C. At high temperature, PNIPAM hydrophobically aggregates into a core, and NDAA self-assembles into a core1 (PNIPAM)–shell (PDMA)–corona1 (P(AM- co -AN)) structure. In contrast, at low temperatures, P(AM- co -AN) forms hydrogen bonds and is insoluble in water, and NDAA self-assembles into a core2 –shell–corona2 structure. In this way, it is possible to prepare spontaneously reversible micellar aggregates in water. After the concentration reaches the lowest critical concentration, the NDAA polymer can undergo a reversible gel behavior, that is, a phase transition occurs near the UCST and LCST. This change in the polarity of the micelle core opens up the possibility of dissolving different compounds in water just by changing the temperature.